การศึกษาสภาพและปัญหาการใช้หลักสูตรชั้นนายพัน เหล่าทหารขนส่ง โรงเรียนทหารขนส่ง กรมการขนส่งทหารบก - สนิทรักษา รัตน์เกล้า; สุดรุ่ง จุไรรัตน์ (An Online Journal of Education, 2018)
The purpose of this research was to study the state and problems on the curriculum implementation of Transportation Officer Advanced Course in Army Transportation School. The respondent are administrators, teachers and trainer and students in Army Transportation School in total of 150 persons. To collect data, the researcher used rate-scale questionnaires. The information and data were analyzed for frequency, distribution, percentage, mean and standard deviation. The results showed that as follows 1) Curriculum administration, it was found that the overall management was in a high level. After considering in each aspect, it was found that the facilitating management was the most performed. The mean was at 4.00. Regarding problems, the mean was in a low level. After considering of each aspect, it was found that the task in recruiting teachers to the class was the problematic. The mean was at 2.85. 2)Instruction, it was found that the overall management was in high level. After considering in each aspect, it was found that understanding the program and making an adjustment in accordance with the conditions and needs of its area was the most performed. The mean was at 3.94. Regarding problems, it was found that the overall management was in a medium level. After considering of each aspect, it was found that remedial teaching was the most problematic.The mean was at 2.98.